'Remember Who You Are Designing For': An Interview with Baroness Sally Greengross OBE. (March 2014) - Greengross, Baroness Sally; Castle, Helen; Farrelly, Lorraine
Abstract Baroness Sally Greengross has a long and deep knowledge of issues surrounding ageing. Until 2000 she was Director General of Age Concern for 13 years, and also joint Chair of the Institute of Gerontology at King's College London and Secretary General of Eurolink Age. She is now President/Chief Executive of the International Longevity Centre‐UK (ILC‐UK), an influential think‐tank impacting policy on longevity, ageing and population change. Since 2000, she has been a crossbench (independent) member of the House of Lords and she chairs five All‐Party Parliamentary Groups: Dementia, Corporate Responsibility, Intergenerational Futures, Continence Care, and Ageing and Older People (Co‐Chair). Here, the Editor of AD, Helen Castle, interviews her on shifting attitudes to ageing and the importance of designing for the older population.